CORPORATE GOVERNANCE, PROFITABILITAS, DAN NILAI PERUSAHAAN - Gusni .; Agnes Vinelda (UNEJ e-Proceeding)
This study aims to examine the effect of corporate governance (board of director, board of commissioner composition, and institutional ownership), profitability (return on asset and net profit margin) on firm value in mining industry, and knowing which variables having powerful effect on the firm value. This research is using secondary data, such as the financial reports, annual reports and other related information of mining industry. To achieve the aims of this research, a total of 20 companies of mining industry listed in Indonesia Stock Exchange were selected using purposive sampling technique from the period of 2010 to 2014. A panel data regression analysis technique has been conducted The research result shows that only profitability variable measured by return on asset (ROA) has a positive and significant effect on the firm value, whereas the other profitability variable measured by net profit margin has a negative and significant effect to the firm value. Meanwhile, corporate governance measured by board of director, board of commissioner composition, and institutional ownership not significantly impact on the firm value in mining industry.